العلاقة بين ممارسات القيادة الموزعة والصراع التنظيمي والرضا الوظيفي لدى العاملين بالمديرية التعليمية في محافظة شمال الباطنة بسلطنة عمان - عوفي، خميس سالم مسعود
This study aimed to demonstrate the relationship between distributed leadership practices, organizational conflict, and job satisfaction among the employees of the Education Directorate in the North Al-Batinah Governorate in the Sultanate of Oman. The study population consisted of (1014) employees while the study sample consisted of (278) employees. The results showed that the practice of distributed leadership by the direct manager was generally to a large degree, and the organizational culture dimension came first, then the joint responsibility dimension, and finally the development dimension. Also, the level of job satisfaction among employees was generally to a large degree, and the dimension of the nature of work came first, then the dimension of motives and incentives. There is a strong and inversely significant relationship at the significance level (α = 0.05) between the degree of practicing distributed leadership and organizational conflict from the employees' point of view. The value of Pearson's correlation coefficient was (-0.77). Also, there is a strong, positive, and statistically significant correlation at the significance level (α = 0.05) between the degree of the practice of distributed leadership and the level of job satisfaction from the employees' point of view. The value of the Pearson correlation coefficient was (0.75). Accordingly, the study recommended enhancing the practices of distributed leadership in the education directorate in the North Al Batinah Governorate, by delegating authority, giving confidence, involving employees in decision-making and applying, and developing their leadership skills through qualification, training, and continuous reinforcement.